Complete guide to television, field and digital producing - Cruikshank, Sally Ann; Eschenfelder, Christine C.; Coleman, Keonte (London Routledge, 2022)
"This book provides an extensive overview of producing in the ever-changing field of journalism for all types of newsrooms. Featuring interviews with renowned journalism professionals, A Complete Guide to Television, Field, and Digital Producing offers an in-depth look at broadcast, field, and digital producing practices of newsrooms today. The book is divided into three sections: television news producing, field producing, and digital producing. Each section provides a clear explanation of the producing role before going into more detail on important skills such as developing stories, writing copy, creating graphics, producing live on location, audience engagement and using social media. Each chapter includes a variety of supplemental material, including discussion questions, keyword definitions, classroom activities, and graded assignments, including rubrics. Written with a combined 64 years of journalism and journalism education experience, the book will prepare students to produce whatever their job requires. Taking an integrated approach to journalism education, this is a vital text for journalism and media students studying digital media, broadcast journalism, social media, and reporting"--
Day in the life of a news producer -- Meet a journalist - profile of a news producer -- Stacking is a dirty word : news judgment and the rundown -- Produce moments and develop stories -- Writing headlines and teases -- Using graphics : the good, the bad, and the ugly -- The producer as a leader, manager, and coach -- Breaking news and live shots -- Commanding the control room -- A conversation with an anchor about news producers -- Self care for journalists -- The ins and outs of field producing -- Meet a journalist - profile of a special projects producer -- Before you leave the newsroom -- Remote location live shows -- Social media from the scene -- Diversity, equity, and inclusion matters : creating a complete story for your audience -- Taking ownership of stories and shows -- Inside and outside the newsroom : law and ethics -- Getting a job as a producer -- Digital producing -- What does a digital producer do? -- Meet a journalist - profile of a digital producer -- Get Googled : SEO best practices -- Creating eye-catching infographics and data visualization -- Producing video inside the newsroom -- Digital producers and social media -- Measuring your audience through metrics -- Behind the paywall.
Includes bibliographical references and index.
Keywords: Television broadcasting of news; Television; Television journalists; Television producers and directors; Television